Disseminated blastomycosis presenting as a retro-orbital mass. Issue 7 (18th July 2019) - Murawski, Shannon; Farrell, Michael; Cordeiro-Rudnisky, Fernanda; Blinkhorn, Richard
Abstract : A 43-year-old man with history of non-Hodgkins' lymphoma presented with unilateral eye swelling, pain and vision deficits which had been progressive over 2 months. Symptoms followed a presumed bacterial pneumonia 4 months prior. Imaging demonstrated retro-orbital soft tissue swelling with bony erosion concerning for a mass; surgical decompression was performed with histology confirming disseminated Blastomyces dermatitidis . Symptoms responded rapidly to antifungal therapy with amphotericin followed by itraconazole. Orbital dissemination of blastomycosis is extremely rare; accurate diagnosis requires tissue biopsy to facilitate timely targeted therapy and minimise morbidity.